Strengthening Organizational Commitment in the Public Sector: The Role of Perceived Organizational Support and Job Satisfaction among Civil Servants - Aribatul Faridhah; Rosita Endang Kusmaryani (Indonesian Journal Publisher, 2026)
Organizational commitment is an important aspect of maintaining employees’ attachment to their organization, particularly in the public sector. This study aimed to examine the relationships between perceived organizational support, job satisfaction, and organizational commitment among ASN employees at DPPKB Kota Bekasi. A quantitative approach with a cross-sectional correlational design was employed. The study population comprised 135 ASN employees, consisting of 94 Civil Servants and 41 Government Employees with Employment Agreements. A total of 101 respondents were selected using purposive sampling. Data were collected using the Organizational Commitment Questionnaire, a perceived organizational support scale, and the Minnesota Satisfaction Questionnaire–Short Form. The data were analyzed using multiple linear regression. The findings indicated that perceived organizational support and job satisfaction were positively associated with organizational commitment. Job satisfaction demonstrated a stronger association with organizational commitment than perceived organizational support. At the dimensional level, extrinsic satisfaction was significantly associated with organizational commitment, whereas intrinsic satisfaction was not. These findings highlight the importance of organizational support and positive work experiences, particularly recognition, supervision, working conditions, and career development, in strengthening employees’ organizational commitment